Virtual Learning 2016
DOI: 10.5772/65222
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Distance Learning and Learning Management Systems

Abstract: In recent years, rapid developments in technology and the web have led to many changes in education. One of the most important changes in education is in the form of distance learning. Distance learning, which is used to define education where educators and learners are physically separated, is not a new concept; however, emerging technologies and the web allow web-based distance learning and therefore increase its popularity. As a result of these developments, many universities have started to use web-based d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 11 publications
0
14
0
1
Order By: Relevance
“…In Australia, a comparative study between distance learning and face to face learning demonstrated how distance learning can enhance enrolments among students as compared to traditional learning (Bookallil and Rolfe, 2016). This is because most of the students believe that distance learning is flexible and more convenient, allows them to make a balance between studying and family or work commitment, developing ICT skills, opportunities to share knowledge and experiences and learn from other (Keles and Özel, 2016;Fincham, 2017).…”
Section: Opportunities and Advantages Of Distance Learningmentioning
confidence: 99%
“…In Australia, a comparative study between distance learning and face to face learning demonstrated how distance learning can enhance enrolments among students as compared to traditional learning (Bookallil and Rolfe, 2016). This is because most of the students believe that distance learning is flexible and more convenient, allows them to make a balance between studying and family or work commitment, developing ICT skills, opportunities to share knowledge and experiences and learn from other (Keles and Özel, 2016;Fincham, 2017).…”
Section: Opportunities and Advantages Of Distance Learningmentioning
confidence: 99%
“…Technology both enables training in terms of connectivity by various means (e.g., mobile learning), but also enhances the training through the use of more interactive tools (e.g., video; graphics; images; simulation). Delivery of such programmes is often facilitated by the use of Learning Management Systems (LMS) such as Moodle, Blackboard, Desire2Learn, Sakai, Docebo, and A Tutor [ 12 ]. These now provide interactive and automated access to many different types of learning content, such as reading materials, video and audio recordings, wikis, web conferencing, chats, forums, blogs, learning games, testing, and grading tools [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…That shall enable instructors to identify the weaknesses of students and address them. It shall enables instructors to identify the gaps in the students' knowledge and the skills that students must develop (Keleş and Özel, 2016).…”
Section: Learning Management Systems: Blackboardmentioning
confidence: 99%
“…It facilitates and improves the interaction between the instructor and his/her students. It enables instructors to observe and analyse the students' behaviours and track students' progress (Keleş and Özel, 2016) Web-based distance education improves students' retention. It facilitates the learning process.…”
Section: Learning Management Systems: Blackboardmentioning
confidence: 99%
See 1 more Smart Citation